Kisah-kisah dan Kepercayaan Rakyat di Seputar Kepurbakalaan - Munandar, Agus Aris (UI Scholars Hub, 2011)
Some archeological sites in Java, Bali, and Sumatra do not have historical data. This is because during the research, there has not been found any documents relating to the existence of the artifacts. The reconstruction of the relation between the sites and their history were made through analyzing the folk stories and local beliefs about the artifacts. Some of the artifacts are in the forms of temples, gates, water springs (source of holy water during the Hindu-Buddhist kingdoms in Java), stairs, caves for meditation, and layers of stones, such as found in Candi Bima (the Bima temple), Goa Jaran (the cave of the horse), and Bima Lukar water spring in Dieng; the story of the statue of Kunto Bimo in Borobudur temple; the story of Prince Gunadharma in the vicinity of the Borobudur temple, Moonstone in Kalasan temple, and the story of Prambanan temple and the palace of Ratu Baka in Jogjakarta, the Jalatunda water spring in Mojokerto; the story of the cave of Selamangleng and the story of the statue of Thothokkerot in Kediri; the Brahu temple and the Bajang Ratu gate in Trowulan; the first gate of Candi Sukuh in Karanganyar; the big Nekara in Pura Penataran Sasih in Gianyar, Bali; the Karang Kamulyan site in Ciamis, West Java; the Pasemah megalith, in Pagar Alam, South Sumatra. Van Peursen’s ontological approach is used in the research to analyze the relation between the artifacts and the society, thus a study of the past is in the open.